HINT2 may be One Clinical Significance Target for Patient with Diabetes Mellitus and Reduced ROS-Induced Oxidative Stress and Ferroptosis by MCU - Bai, Mei; Lu, Wei; Tan, Jun; Mei, Xin (Hormone and Metabolic Research, 2024)
The World Health Organization (WHO) predicted that patients with diabetes around the world will increase to 600 million by 2040, of which about 1/3 will develop diabetic nephropathy (DN). Therefore, the present study aimed to uncover therapeutic effect of HINT2 and determined its possible mechanisms. Patients with diabetes mellitus and normal volunteers were enrolled at our hospital. Male C57BL/6 mice were fed with a high fat diet and injected intraperitoneally with STZ for once (100 mg/kg body weight). Mouse podocytes (MPC5) cells were induced with 20 mmol/l D-glucose. Inhibition of HINT2 mRNA expression levels in patients with DN was observed, compared with normal group. The serum of HINT2 mRNA expression was negative in correlation with blood sugar, tubulo-interstitial damage, glomerular damage score or urine protein level in patients with DN. HINT2 expression in kidney tissue of mice with DN were downregulated. HINT2 presented reduced DN and inflammation and ROS-induced oxidative stress in model of DN. HINT2 promoted ferroptosis in model of DN by mitochondrial membrane potential. HINT2 suppressed MCU expression in model of DN. HINT2 protein combined with MCU protein increased MCU protein ubiquitination. HINT2 triggers mitochondrial Ca2+ influx to increase ROS production level by MCU. Taken together, these findings demonstrated that HINT2 reduced ROS-induced Oxidative stress and ferroptosis by MCU, suggesting that HINT2 may be a feasible strategy to treat DN.
Keywords: HINT2; ROS-induced oxidative stress; ferroptosis; MCU; diabetic nephropathy